Psychological Intervention for Postpartum Depression - 姜蕾 王竹珍 邱丽蓉 万国斌 林艳 韦臻 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Summary： The postpartum depression outcome and the effect of psychological intervention were studied in order to reduce the occurrence and development of the postpartum depression. A survey of 4000 women within 4-6 weeks postpartum in 80 communities in Shenzhen, China was performed using random cluster sampling method. By employing Edinburgh Postnatal Depression Scale （EPDS） as a screening tool, the positive women （defined as EPDS 〉10） were randomly divided into intervention group and control group at a ratio of 1：2. The women in the intervention group were treated by means of mailing postpartum depression prevention and treatment knowledge manual, face-to-face counseling, and telephone psychological counseling interventions aiming at individual risk factors, while those in the control group were treated with conventional methods. EPDS scores were assessed in these two groups again at 6th month postpartum. Totally, 3907 valid questionnaires were obtained. All the 771 positive women were divided into two groups： 257 in the intervention group, and 514 in the control group. At 6th month postpartum, the EPDS scores in the intervention group were decreased significantly, from baseline stage （12.84±3.02） to end stage （3.05±2.93）, while EPDS scores in the control group were reduced from 12.44±2.78 to 6.94±4.02. There were significant differences in the EPDS scores at end stage between the two groups （t=13.059, P〈0.001）. Psychological intervention can reduce postpartum depression, with better maternal compliance. It is feasible and necessary to establish postpartum depression screening and psychological intervention model in community-hospital and include the postpartum depression screening, intervention, and follow-up into the conventional healthcare.